Strategi Orang Tua Dalam Perkembangan Anak Usia Dini di Era Metaverse - Saflitha, Widya; Sehati, Rindu; Wahyuni, Sri; Siregar, Arinil Haq (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine parents' strategies in integrating metaverse in early childhood development, considering the significant changes in the way children learn and interact in the fast-paced digital era. This study explores how metaverse, as a platform that enables immersive and interactive learning and socialization experiences, is used by parents to support their children's cognitive, social, and emotional development. Through in-depth qualitative analysis, this study uses a descriptive approach to systematically describe and analyze this phenomenon, with data collected through observation, documentation, and in-depth interviews with parents. The data analysis technique follows the Miles, Huberman, and Saldana model, with data validity checks through source triangulation. The results of the study are expected to provide valuable insights into how parents can utilize metaverse for effective parenting, as well as support the formation of policies and practices that ensure the safe and inclusive use of technology in early childhood care.